2023
DOI: 10.1021/acs.jmedchem.3c00505
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Potent, Selective, and In Vivo Efficacious Polo-like Kinase 4 Proteolysis Targeting Chimera Degrader for the Treatment of TRIM37-Amplified Breast Cancer

Abstract: Polo-like kinase 4 (PLK4) is a master regulator of centriole replication and has been proposed as a therapeutic target for multiple cancers, especially TRIM37-amplified breast cancer. The development of novel and effective therapeutic strategies for TRIM37-amplified breast cancer therapy is challenging and extremely desirable. Herein, a structure−activity relationship (SAR) study with an emphasis on exploring different linker lengths and compositions was performed to report the discovery and characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…Studies revealed that TRIM37 blocks the formation of foci that comprise pericentriolar material—these foci are structures with a microtubule‐nucleating capacity, which is required for correct cell division in the absence of centrosomes. 204 , 205 Interestingly, researchers found an excess of TRIM37 leads to synthetic lethality with the polo‐like kinase 4 (PLK4) inhibitor, which provides a rationale for the use of centrosome targeting agents in treating tumors bearing TRIM37 overexpression. Notably, the TRIM37 is located in the chromosomal region 17q23, which is frequently amplified in several tumor types, including about 10% of BC cases.…”
Section: The Roles Of Trims In Bcmentioning
confidence: 99%
“…Studies revealed that TRIM37 blocks the formation of foci that comprise pericentriolar material—these foci are structures with a microtubule‐nucleating capacity, which is required for correct cell division in the absence of centrosomes. 204 , 205 Interestingly, researchers found an excess of TRIM37 leads to synthetic lethality with the polo‐like kinase 4 (PLK4) inhibitor, which provides a rationale for the use of centrosome targeting agents in treating tumors bearing TRIM37 overexpression. Notably, the TRIM37 is located in the chromosomal region 17q23, which is frequently amplified in several tumor types, including about 10% of BC cases.…”
Section: The Roles Of Trims In Bcmentioning
confidence: 99%